Comparing Telerehabilitation and In-Person Interventions in School-Based Occupational Therapy for Specific Learning Disorder A Randomized Controlled Trial: Exploring Efficacy, Academic Impact, and Parental Satisfaction in a Novel Approach to Addressing Specific Learning Disorders in Children - kheirollahzadeh, mahsa; Azad, Akram; Saneii, Seyed Hassan; Alizadeh Zarei, Mehdi (Iranian Journal of Child Neurology, 2024)
Objective This study investigated the efficacy of telerehabilitation (TR) in school-based Occupational Therapy (OT) for children with Specific Learning Disorder (SLD), focusing on occupational competence and parental satisfaction, aiming to contribute empirical insights to the discourse on the educational well-being of this population. Materials & Methods The study adopted a Randomized Controlled Trial (RCT) design involving 31 children diagnosed with SLD, implementing TR and inperson interventions alongside a control group. Outcome measures included the School Self-Concept Inventory, Child Occupational Self-Assessment (COSA), and Canadian Occupational Performance Measurement (COMP), analyzed using descriptive and inferential statistics (ANOVA, post hoc tests). Results Both TR and in-person interventions exhibited significant enhancements in academic self-efficacy (F=23.96, p<0.001, Partial ȵ²=0.461), occupational competence (F=70.59, p<0.001, Partial ȵ²=0.716), and parent satisfaction (F=17.03, p<0.001, Partial ȵ²=0.378) compared to the control group. Notably, no significant differences emerged between the TR and in-person groups, emphasizing their comparable effectiveness in improving outcomes. Conclusion In conclusion, the study demonstrated the efficacy of TR and inperson interventions in school-based OT for children with SLD. The cohesive outcomes in academic self-efficacy, occupational competence, and parental satisfaction highlight TR as a versatile modality. This research, grounded in robust methodology, encourages further exploration of TR’s transformative role in enhancing the holistic well-being of children with SLDs